Novel approaches to anti-obesity drug discovery with gut hormones over the past 10 years. (2nd November 2019) - Rose, Frances; Bloom, Stephen; Tan, Tricia
ABSTRACT: Introduction : Obesity is a global pandemic and new pharmacotherapies which combine weight loss efficacy, long-term safety, and reversal of metabolic co-morbidities are sorely needed. Gut hormones play key roles in regulating satiety and metabolism, and are natural candidates for therapeutic development. Areas covered : The authors discuss recent drug developments for the treatment of obesity using gut hormones. The review was based on a search of PubMed using keywords 'obesity' AND ('therapy' OR 'pharmacotherapy' OR 'gut hormones' OR 'analogues'), limited to the last 10 years. Expert opinion : Analogues of glucagon-like peptide (GLP-1) have been developed for obesity but so far do not provide enough weight loss. Bariatric surgery increases the post-prandial secretion of multiple gut hormones, leading to beneficial effects on weight loss and metabolism. This recognition has led to poly-agonist strategies: GLP-1/glucagon or GLP-1/glucose-dependent insulinotropic peptide (GIP) dual agonism, or even GLP-1/glucagon/GIP triple agonism. New delivery approaches include peptide-conjugate therapies that target key metabolic tissues. Practicable methods for oral delivery of peptide gut hormones are also close to market, expanding the potential market for these treatments. Anti-obesity therapy is therefore poised for an exciting phase, and it will be interesting to see which of these will eventually prevail.